Antifungal activity of moringa (Moringa oleifera) leaf extracts against major plant pathogens - MAJUMDER, SUJAN; RANI, VIJAYA; SINGH, SATYAPRIYA; SRIVASTAVA, KULDEEP (The Indian Journal of Agricultural Sciences, 2024)
Widespread use of chemical pesticides leads to soil and water pollution with harvest detrimental to human health. A viable alternative is to use environment-friendly substitutes that do not possess residue problems. Moringa is popularly known as “the tree of life” as each part of the tree has some medicinal attributes. An attempt was made to explore the use of moringa extracts for plant disease management. Moringa leaves were extracted with different solvents (water, acetone, ethyl acetate and hexane) and tested against major soil-borne pathogens (Athelia rolfsii, Rhizoctonia solani and Fusarium spp.). The leaf extracts showed an inhibitory effect on the growth of all the pathogens. Significantly higher inhibition was observed in plates where water was used for the extraction of bioactive compounds. The ED50 value of 546.51 mg/litre was reported for the pathogen Athelia rolfsii when water was used for extraction followed by acetone (624.25 mg/litre) and ethyl acetate (680.75 mg/ litre). The inhibition percentage and ED50 value varied significantly with the change in the solvent used for the extraction purpose. According to the results, moringa leaf extracts can be utilized as a good substitute for chemical pesticides since they are efficient against plant pathogens.